Farm credit, farmland, farm infrastructure and agricultural output in Kano State, Nigeria : the moderating effect of murabahah finance - Mohammed, Ahmed Ibrahim (2017)
The purpose of this study is to investigate the relationship between farm credit, farm land, farm infrastructure and agricultural output in Kano State, Nigeria with the effect of Murabahah finance. Literature was extensively reviewed in agriculture and other related fields for better understanding of past, present and future needs in the study area. Although their relationships have generated considerable scholarly interest, few studies have actually been conducted among agricultural output in Nigeria. Agriculture is essential to economic growth in Nigeria and it is a major source of employment and poverty reduction as well as contributing significantly towards the gross domestic products. Based on a theoretical consideration, a model was proposed to examine these relationships. A cross-sectional survey design was adopted and the unit of analysis was the individual, which is small scale farmers in Kano State, Nigeria; were the respondents. The study employed systematic sampling technique in data collection, with a sample size of 764 farmers. Likewise, Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the study‘s hypotheses. The findings of this study reported that farm credit, farm land and farm infrastructure have a direct significant positive relationship with agricultural output in Kano State, Nigeria. The result of hierarchical regression (moderation test) established that Murabahah finance was found to moderate the relationships between farm credit and farm land while, farm infrastructure was not found moderated. Finally, study's implications for theory and practice, limitations, conclusions as well as direction for future research were provided and discussed.